India’s Growing Demand of Nutraceuticals - Ahmad, Saqlain (Asian Journal of Pharmaceutical Research and Development, 2024)
Nutraceuticals are nutritive ingredients—a cross between food and medicine—that are physiologically active and have the power to preserve optimum health and advantages. These goods are essential to maintaining human health and well-being, especially in light of upcoming treatment advancements. Due to their safety profile, medicinal effects, and nutritional advantages, nutraceuticals have gained popularity. Global demand for nutraceuticals is rising in the areas of disease prevention, health care promotion, and other services. In this overview, several drug-nutritional interactions are additionally outlined using a variety of instances. The concluding portion of the assessment states that there are several patents on nutraceuticals for use in agriculture and in treating a variety of disorders, confirming the exponential rise of the market for nutraceuticals. In addition to being used for nutrition, nutraceuticals have been employed as an adjunct treatment for both the prevention and the treatment of a number of disorders, including the reduction of adverse effects from radiation and chemotherapy for cancer. Nutraceutical formulation development presents a number of obstacles that are often solved by a variety of innovative nano-formulation techniques. Any negative effects of nutraceuticals products may be avoided with the aid of prior knowledge about different medication combinations. Moreover, micronized food items along with additional nutraceutical supplements with enhanced health advantages are produced thanks to nanotechnology. The most recent significant results (clinical research) on nutraceuticals that demonstrate the bioactive compounds in these supplements have a therapeutic effect on a range of ailments have also been included in this review article.